RESULTS OF RADIOSURGICAL AND DRUG TREATMENT OF PATIENTS WITH BRAIN METASTASES - S. M. Banov; A. V. Golanov; S. R. Ilyalov; E. R. Vetlova; S. A. Maryashev; D. R. Naskhletashvili; I. K. Osinov; V. V. Kostuchenko; A. A. Durgaryan (Опухоли головы и шеи, 2017)
The study objective is to study overall survival and the rate of intracranial recurrences in patients with brain metastases after radiosurgery as single treatment.Materials and methods. The results of radiosurgical treatment of 579 patients with brain metastases (248 men and 331 women) were analyzed. The sources of brain metastases were breast cancer (164 patients), non-small-cell lung carcinoma (162), melanoma (123), kidney cancer (87), colorectal cancer (43). Median cumulative tumor volume, maximal lesion volume, number of brain metastases in the studied patient group were 5.4 cm3, 3.6 cm3, and 4, respectively. Mean marginal dose of ionizing radiation was 22 Gy (15–24 Gy). Mean follow-up duration was 13.4 months.Results. Overall survival of patients at 12 and 24 months was 42.8 and 24.8 %, respectively, with median overall survival after radiosurgery of 9.8 months (95 % confidence interval: 8.5–11.3). Local control of metastatic lesions was achieved in 81.3 % patients. Survival without local recurrence at 12 months was 66.7 %. Distant metastases developed in 235 (52.4 %) of 449 patients for whom radiological data was available. Survival without distant metastases at 12 and 24 months was 41.5 and 20.9 %, respectively. Multifactor analysis has shown that prognostic factors for long-term survival in patients with brain metastases were presence of breast cancer metastases in the brain, limited (4 lesions or less) number of brain metastases, high functional status, and absence of extracranial metastases. Increased survival duration was also associated with targeted therapy (p = 0.0412) and repeated radiosurgery to treat intracranial recurrences (р <0.0001).Conclusion. Radiosurgical treatment of patients with brain metastases confers higher median overall survival (up to 9.8 months) than the same criterion (7.1 months) in the 1st class patients (per the recursive partitioning analysis scale) who received irradiation of the whole brain as single treatment. Repeated radiosurgery in cases of intracranial recurrences and targeted therapy confer increased overall survival of patients with brain metastases.